Treatment of de Quervain's Tenosynovitis with Prolotherapy: A Case Report - Veronika Susanty Siampa; Charles Wijaya Tan (HM Publisher, 2023)
Introduction: De Quervain's tenosynovitis is a disease with pain in the styloid process area due to chronic inflammation of the tendons covering the abductor pollicis longus and extensor pollicis brevis muscles at the level of the distal radius. This study aims to describe the treatment of de Quervain's tenosynovitis with prolotherapy. Case presentation: A woman, 49 years old, working as a cleaning service, came to the hospital with complaints of pain in her right thumb and wrist. Pain has been felt since 1.5 years ago, especially when using the hand and moving the thumb. The pain has been getting worse in the last 4 months and is sometimes swollen and red near the thumb. Physical examination showed nodules measuring 2x1 cm in the right radial region, positive tenderness, positive Allen test, active and passive movement of digit 1, rotation and adduction inhibition, wrist extension and digitorum positive, wrist flexion and digitorum positive, and a positive Finkelstein test. The patient was diagnosed with de Quervain's tenosynovitis dextra. Prolotherapy was carried out as pain management in this patient. Conclusion: Treatment with injection prolotherapy of patients with complaints of de Quervain's tenosynovitis using a mixture of D40% solution and lidocaine has a good prognosis for symptom improvement and relatively minimal complications.